2018
DOI: 10.2340/00015555-2756
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy: Influence of Clinical and Procedure Variables on Treatment Response in Basal Cell Carcinoma and Bowen Disease

Abstract: This is an open access article under the CC BY-NC license. www.medicaljournals.se/acta Acta Derm Venereol 2018; 98: 116-118 116 Photodynamic therapy (PDT) is one of the most commonly used non-invasive treatments in non-melanoma skin cancer (NMSC). High rates of complete remission can be obtained using PDT with methyl-aminolevulinate (MAL); for basal cell carcinoma (BCC) the response rate is 91% at 3 months and 76% at 5 years, with 5-year recurrence rates of 22% in superficial BCC (sBCC) and 14% in nodular BCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…According to our findings, the H area is the least suitable area for PDT, it can be explained because they are embryological fusion areas with a tendency to invade in depth or maybe the locations of lesions reflect accumulation of UV lesions and hence, status of mutations. [20] In our series of 472 tumors (BCC and Bowen disease) treated with MAL-PDT, we found that more advanced age was a predictor of a poor response. Supporting this view, Niessen et al .…”
Section: Discussionmentioning
confidence: 95%
“…According to our findings, the H area is the least suitable area for PDT, it can be explained because they are embryological fusion areas with a tendency to invade in depth or maybe the locations of lesions reflect accumulation of UV lesions and hence, status of mutations. [20] In our series of 472 tumors (BCC and Bowen disease) treated with MAL-PDT, we found that more advanced age was a predictor of a poor response. Supporting this view, Niessen et al .…”
Section: Discussionmentioning
confidence: 95%
“…However, in some cases, resistance of BCCs to clinical treatments occurs 2127 . In the case of PDT for BCC, detection of recurrences after treatment has been as high as up to 30% 2830 . Therefore, understanding the resistant mechanisms to PDT constitutes a very important goal for the management of BCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies based on longer follow-up periods are based on diverse methods, which makes comparison difficult. [4][5][6][7][8][9][10] The aims of the present study were to review usual clinical practice in the treatment of Bowen's disease with photodynamic therapy, over an extended study period (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) at a third-level hospital, to evaluate the long-term efficacy of photodynamic therapy with methyl aminolevulinate (MAL-PDT) and to identify the risk factors associated with the response rate.…”
Section: Introductionmentioning
confidence: 99%
“…Although it appears to be a highly effective treatment for this type of neoplasm (response rates vary from 52% to 100%), some research papers have reported significant long‐term recurrence. However, studies based on longer follow‐up periods are based on diverse methods, which makes comparison difficult …”
Section: Introductionmentioning
confidence: 99%